Mapping and Analysis of Rainfall in Purbalingga Regency for Settlement Suitability - Dyah Rizky Alyudin; Adi Wibowo (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract:  The suitability of settlements can be seen from the intensity of rainfall. The high and low intensity of rainfall can be used as a reference for whether a settlement is suitable or not. Areas with very high and very low rainfall can be categorized as areas that are not suitable for settlements, while areas with moderate rainfall can be grouped into areas that are very suitable for settlements based on indications of the possibility of disasters. This analysis was obtained through climatological analysis from SCOPIC. The results show that However, these indications are difficult to associate with the drought and wetness indexes from existing rainfall data, it is difficult to associate with indications of drought or other potential hydrometeorological disasters, considering that rainfall in Purbalingga Regency is not too affected by the SPI index system such as El Nino and La Nina, so that settlement suitability is made based on the rainfall category alone, where Karangreja, Kutasari, Padamara, Kalimanah, Purbalingga, Kemangkon and Bukateja Districts are included in the category of areas that are very suitable and suitable for settlements.Abstrak: Kesesuaian permukiman salah satunya dapat dilihat melalui intensitas curah hujan. Tinggi rendahnya intensitas curah hujan dapat dijadikan acuan layak atau tidaknya suatu pemukiman. Wilayah dengan curah hujan sangat tinggi dan sangat rendah dapat dikategorikan sebagai wilayah yang tidak layak untuk pemukiman, sedangkan wilayah dengan curah hujan sedang dapat dikelompokkan ke dalam wilayah yang sangat layak untuk pemukiman berdasarkan indikasi kemungkinan terjadinya bencana. Analisis ini didapatkan melalui analisis klimatologis dari SCOPIC. Hasil menunjukkan bahwa   indeks kekeringan dan kebasahan dari data curah hujan yang ada sulit untuk dikaitkan dengan indikasi kekeringan maupun potensi bencana hidrometeorologis lain, mengingat curah hujan di Kabupaten Purbalingga tidak terlalu terpengaruh oleh sistem indeks SPI seperti El Nino dan La Nina, sehingga kesesuaian permukiman dibuat berdasarkan pada kategori curah hujan saja, dimana Kecamatan Karangreja, Kutasari, Padamara, Kalimanah, Purbalingga, Kemangkon dan Bukateja termasuk dalam kategori wilayah yang sangat layak dan layak untuk dijadikan pemukiman.